Control And Reward In Online Dating Practices – A Study Of Users’ Experiences Of Tinder - Rosén, Anton; Lundmark, Sofia; Jonsson, Fatima; Håkansson, Jesper (AoIR Selected Papers of Internet Research, 2017)
This paper is based on a study of users experiences and practices of meeting potential new partners online through the use of the mobile dating service Tinder. The aim of the study is to explore how users experience design features and functionalities for online dating practices. By exploring the use of functionalities and features in the location-based mobile application Tinder, we offer a broad understanding of the relationship between designed functionalities and dating practices that users experience through these features. The empirical material presented in the paper is drawn from a study based on a mixed method approach, combining an initial observational study, an online survey, with focus group interviews. Four specific designed functions are highlighted in our empirical data: the connection with Facebook, the profile cards of users, the swipe-centered mutual match function, and geographical proximity. These functions contribute to the specific user experiences of control and reward. Our findings indicate that online dating practices are formed by an inseparable interplay of design functionalities, users attitudes and the use of specific mobile applications that taken together contributes to the overall online dating experiences.